A Revolutionary Blueprint for Mitigation of Hypertension via Nanoemulsion. (14th April 2022) - Kumar, Girish; Virmani, Tarun; Pathak, Kamla; Alhalmi, Abdulsalam
Abstract : Hypertension is one of the most important causes of mortality, affecting the health status of the patient. At the same time, hypertension causes a huge health and economic burden on the whole world. The incidence and prevalence of hypertension are rising even among young people in both urban as well as rural communities. Although various conventional therapeutic moieties are available for the management of hypertension, they have serious flaws such as hepatic metabolism, reduced dose frequency, poor aqueous solubility, reduced bioavailability, and increased adverse effects, making the drug therapy ineffective. Therefore, it is required to design a novel drug delivery system having the capability to solve the constraints associated with conventional treatment of hypertension. Nanotechnology is a new way of using and manipulating the matter at the molecular level, whose functional organization is measured in nanometers. The applications of nanotechnology in the field of medicine provide an alternative and novel direction for the treatment of cardiovascular diseases and show excellent performance in the field of targeted drug therapy. Various nanotechnologies based drug delivery systems, such as solid lipid nanoparticles, nanosuspension, nanoemulsion, liposome, self-emulsifying systems, and polymeric nanoparticles, are available. Among them, nanoemulsion has provided a niche to supplement currently available therapeutic choices due to numerous benefits like stability, ease of preparation, enhanced drug absorption, reduced hepatic metabolism, increased dose frequency, enhanced bioavailability, and encapsulation of hydrophilic as well as hydrophobic drugs. This present review provides an in-depth idea about progression in treatment of hypertension, constraints for antihypertensive drug therapy, need of nanoemulsions to overcome these constraints, comparative analysis of nanoemulsions over other nanostructure drug delivery systems, pharmacodynamics studies of nanoemulsions for treatment of hypertension, recent patents for drug-loaded nanoemulsions meant for hypertension, and marketed formulations of nanoemulsions for hypertension.